Work from home: A behavioral model of Indonesian education workers' productivity during Covid-19. Issue 3 (March 2023) - Suhariadi, Fendy; Sugiarti, Rini; Hardaningtyas, Dwi; Mulyati, Rina; Kurniasari, Evi; Saadah, Nurlailis; Yumni, Hilmi; Abbas, Ansar
Abstract: Although it is not a new phenomenon, many present employees have not previously encountered it. The Covid-19 outbreak has turned the concept of Work from Home (WFH) into a legally regulated and severely enforced norm, which is now in effect. This idea is vital for developing practical organizational policies and procedures in the future in specific educational sectors pertinent to academics. The effectiveness of an individual's ability to cope with WFH was evaluated using a theoretical framework created to measure productivity. The model was evaluated on individuals from a top-ranking public university in Indonesia, chosen as the target population. A total number of 556 respondents responded to the survey questionnaire. AMOS was used to analyze statistical responses related to job crafting, work stress, organizational support, boredom, work engagement, productivity, and mental health. The structural equation analysis, also known as the SEM, was used for this work's measurement model. The findings revealed that the productive conduct of teaching teachers and staff played a substantial role in the success of the work-from-home situation. Conclusions The findings of this study indicate that the indicators used to measure productive behavior while working from home are accurate. As a result, the hypothesis has been proven correct. The study's ecological implications are explained in the relevant sections of this paper.